Behcet Disease With Vascular Involvement Effects of Different Therapeutic Regimens on the Incidence of New Relapses - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2015)
Vascular involvement is one of the major causes of mortality and morbidity in Behcet disease (BD). There are no controlled studies for the management of vascular BD (VBD), and according to the EULAR recommendations, only immunosuppressive (IS) agents are recommended. In this study, we aimed to investigate the therapeutic approaches chosen by Turkish physicians during the initial event and relapses of VBD and the association of different treatment options with the relapses retrospectively. Patients with BD (n = 936, female/male: 347/589, mean age: 37.6 +/- 10.8) classified according to ISG criteria from 15 rheumatology centers in Turkey were included. The demographic data, clinical characteristics of the first vascular event and relapses, treatment protocols, and data about complications were acquired. VBD was observed in 27.7% (n = 260) of the patients during follow-up. In 57.3% of the VBD patients, vascular involvement was the presenting sign of the disease. After the first vascular event, ISs were given to 88.8% and AC treatment to 59.8% of the patients. Median duration of AC treatment was 13 months (1-204) and ISs, 22 months (1-204). Minor hemorrhage related to AC treatment was observed in 7 (4.7%) patients. Asecond vascular event developed in 32.9% (n = 86) of the patients. The vascular relapse rate was similar between patients taking only ISs and AC plus IS treatments after the first vascular event (29.1% vs 22.4%, P = 0.28) and was significantly higher in group taking only ACs than taking only ISs (91.6% vs 29.1%, P < 0.001). During follow-up, a third vascular event developed in 17 (n = 6.5%) patients. The relapse rate was also similar between the patients taking only ISs and AC plus IS treatments after second vascular event (25.3% vs 20.8%, P = 0.93). When multivariate analysis was performed, development of vascular relapse negatively correlated with only IS treatments. We did not find any additional positive effect of AC treatment used in combination with ISs in the course of vascular involvement in patients with BD. Severe complications related to AC treatment were also not detected. Our results suggest that short duration of IS treatments and compliance issues of treatment are the major problems in VBD associated with vascular relapses during follow-up.
Keywords: THROMBOSIS; MORTALITY